Radix Entomolaris - Filloy DDS, Carlos (2015)
A comprehensive knowledge of the root canal morphology and its variations is a basic requisite for the success of the endodontic treatment. Mandibular molars may present a third or additional root, which if located lingually is called radix entomolaris or bucally is referred as radix paramolaris. This case report shows an endodontic retreatment of a radix entomolaris and details some variations in the approach to guarantee a successful terapy.